Evaluation of optimal conditions for arginase activity in streptozotocin induced diabetic rats - Erisir, M; Ercel, E; Yilmaz, S; Ozan, S (Czech Academy Agricultural Sciences, 2005)
The assay conditions needed to achieve maximal activity of liver and kidney arginase in diabetic and non-diabetic rats were investigated and compared. The physicochemical and kinetic properties of liver arginase in diabetic and control rats were very similar, those of kidney arginase were significantly different. It was found that preincubation temperature (68 degrees C), preincubation period (20 min), optimum pH (10.1) of liver arginase and K (3.2) for its substrate, L-arginine, did not change in diabetic and non-diabetic rats. As a consequence of diabetes, the optimum Mn2+ concentration for liver arginase only changed from 1 to 2 mM. Although the preincubation temperature and period for activation of kidney arginase in control rats was unnecessary, they were found to be 56 degrees C and 12 min in diabetic rats. The pH profile of arginase in kidney of diabetic rats was different from that of control rats. The K. value (6.7) of arginase for L-arginine in kidney is unchanged in diabetes whereas a marked decrease in V-max was found. Optimum Mn2+ concentration (2 mM) for kidney arginase was unchanged in diabetes. The activity of arginase in liver of diabetic animals was higher 1.5 to 1.7 times than that of controls. Diabetes caused an about 53% decrease of arginase activity in kidney of female rats, 26% in that of males. These findings may suggest an idea that encoded arginases by separate gene loci may be affected differently by the pathological and hormonal status.
Keywords: arginase; diabetes; physicochemical and kinetic properties